Social Psychological Description of Adolescent Aggressive Behavior - Kushanova Mashkhura Isakovna (International Journal on Integrated Education, 2022)
This article discusses the fact that the problem of aggressive behavior of adolescents is one of the current problems of world science and scientific research centers, and the forms of prevention and elimination of the problem of aggressive behavior. In the process of studying this problem, special attention is paid to the causes of aggressive behavior observed in teenagers. The definitions given by local and foreign scientists to the concept of aggressiveness are analyzed. In addition, conclusions on the prevention and elimination of aggression in adolescents are presented.